Two Splicing Variants of OsNPF7.7 Regulate Shoot Branching and Nitrogen Utilization Efficiency in Rice - Huang, Weiting; Bai, Genxiang; Wang, Jie; Zhu, Wei; Zeng, Qisen; Lu, Kai; Sun, Shiyong; Fang, Zhongming (Frontiers in Plant Science, 2018)
Rice includes 93 nitrate and peptide transporters family (NPF) members that facilitate the soil uptake and internal reallocation of nitrogen for growth and development. This study demonstrated that OsNPF7.7 had two splicing variants, and altered expression of each variant could regulate shoot branching and nitrogen utilization efficiency in rice. The expression of both variants was down-regulated in the buds by increased nitrogen levels in ZH11. The expression level of long-variant OsNPF7.7-1 was higher in panicles at reproductive stage, however, the expression level of short-variant OsNPF7.7-2 was higher in buds and leaves at vegetative stage compared to each other in ZH11. OsNPF7.7-1 was localized in the plasma membrane, whereas OsNPF7.7-2 was localized in the vacuole membrane. Furthermore, the results indicated that the expression level of each variant for OsNPF7.7 determined axillary bud outgrowth, and then influenced the rice tiller number. Overexpression of OsNPF7.7-1 could promote nitrate influx and concentration in root, whereas overexpression of OsNPF7.7-2 could improve ammonium influx and concentration in root. RNAi and osnpf7.7 lines of OsNPF7.7 showed an increased amount of amino acids in leaf sheaths, but a decreased amount in leaf blades, which affected nitrogen allocation and plant growth. The elevated expression of each variant for OsNPF7.7 in ZH11 enhanced nitrogen utilization efficiency using certain fertilization regimes under paddy field conditions. Moreover, overexpression of each variant for OsNPF7.7 in KY131 increased significantly the filled grain number per plant. Thus, increased each variant of OsNPF7.7 has the potential to improve grain yield and nitrogen utilization efficiency in rice.